(untitled) (Medical Forum Monthly, 2022)
Objective: This study was to explore the need for reproductive health education among medical students as the students are ignorant regarding the education of reproductive health before their marriages. Study Design: Qualitative exploratory study Place and Duration of Study: This study was conducted at the Sir Syed Medical College for Girls, and Al-Tibri Medical College and Hospital. Karachi, from March to July 2020. Materials and Methods: This study was conducted among the medical students from two different Institute. The studied sample consisted of students of all the medical years. We conducted a total of 14 focus groups and 12 in-depth interviews. Hence, a purposive sampling technique was used to collect the data. The content analysis method was used to analyze the data. According to the perceptions of participants, various themes were identified, such as (1) lack of reproductive health knowledge, (2) barriers to avail reproductive health services, (3) consequences of an individual and (4) social-cultural consequences. Results: Twenty-six medical students, both married and unmarried, were included belonging to the age group of 18–25 years were interviewed. A lack of knowledge regarding sexual reproductive health was seen among the medical students of Karachi. Girls and women in our country hardly learn from their parents and teachers regarding reproductive health. Conclusion: The need for reproductive health education was being prioritized by most of the participants, not because of the diseases associated with reproductive health but also because of other issues individuals face.